The WTP for Facilities at the Amsterdam Zuidas - Thomas de Graaff; Henri L.F. de Groot; Caroline A. Rodenburg; Erik T. Verhoef (Tinbergen Institute, 2005)
This paper reports the results of a stated preference study investigating the Willingness-to-pay (WTP) of employees at the Amsterdam Zuidas for the presence of non-shopping and shopping facilities. The Amsterdam Zuidas area, surrounding the current train-metro-tram station Amsterdam Zuid World-Trade-Centre, is the largest multifunctional land use project currently under development in The Netherlands. For non-shopping facilities, the results show that employees have the highest WTP for the presence of day-care centres and public transport facilities, and the lowest for public and recreation facilities. The average WTP for the presence of non-shopping facilities amounts to approximately exteuro 29 per month per employee. The WTP for the presence of shopping facilities is estimated at exteuro 16 per month per employee on average, and is in absolute value highest for supermarkets and lowest for hairdressers and dry cleaners.
Keywords: C42; R14; 330; Multifunctional Land Use; Roy's Selection Model; Stated Preference Survey; Willingness to Pay